ASPEK MORALITAS NOVEL RANTAU 1 MUARA KARYA AHMAD FUADI RELEVANSI BAHAN AJAR SASTRA - Santika, Desintia Mutiara; Saputri, Hidayah Nurul; Sudiatmi, Titik (Bahasa Indonesia Prima, 2023)
The research used a qualitative descriptive method; the descriptive presentation was carried out according to facts and phenomena, not in the form of numbers or writing variables with the title